2024
DOI: 10.1021/acsnano.3c10810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Peptoid Sequence on the Mechanisms and Kinetics of 2D Assembly

Sakshi Yadav Schmid,
Xiang Ma,
Joshua A. Hammons
et al.

Abstract: Two-dimensional (2D) materials have attracted intense interest due to their potential for applications in fields ranging from chemical sensing to catalysis, energy storage, and biomedicine. Recently, peptoids, a class of biomimetic sequence-defined polymers, have been found to self-assemble into 2D crystalline sheets that exhibit unusual properties, such as high chemical stability and the ability to self-repair. The structure of a peptoid is close to that of a peptide except that the side chains are appended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Structural analyses revealed that the nanosheet surfaces were sheltered by the hydrophilic heads, whereas the hydrophobic tails were shown to be at the interior of the nanosheets. A recent study outlined the successful formation of 2D sheet structures involving amphiphilic peptoid sequences ( 79 – 81 ) at solution–solid interfaces via hydrophobic, π–π stacking, and hydrogen bonding interactions . However, all three sequences displayed similar growth patterns, and the rate of surface coverage was observed to be the highest for sequence 79 , followed by 80 and then 81 at similar concentrations (Figure e–g).…”
Section: D Architectures By Programmable Fabrication Strategiesmentioning
confidence: 86%
See 1 more Smart Citation
“…Structural analyses revealed that the nanosheet surfaces were sheltered by the hydrophilic heads, whereas the hydrophobic tails were shown to be at the interior of the nanosheets. A recent study outlined the successful formation of 2D sheet structures involving amphiphilic peptoid sequences ( 79 – 81 ) at solution–solid interfaces via hydrophobic, π–π stacking, and hydrogen bonding interactions . However, all three sequences displayed similar growth patterns, and the rate of surface coverage was observed to be the highest for sequence 79 , followed by 80 and then 81 at similar concentrations (Figure e–g).…”
Section: D Architectures By Programmable Fabrication Strategiesmentioning
confidence: 86%
“…Copyright 2020 Royal Society of Chemistry. Panels (e–g) were adapted from ref . Copyright 2024 American Chemical Society.…”
Section: D Architectures By Programmable Fabrication Strategiesmentioning
confidence: 99%